“If only you could see me now”: Autoportrait et théâtralité dans les lettres de Sylvia Plath à sa mère - Laure DE NERVAUX-GAVOTY (E-REA)
Sylvia Plath's work is haunted by the question of self-representation; her poems, her autobiographical novel The Bell Jar, her short stories, her diary, and her correspondence can be read as facets of a self-portrait diffracted through the different mirrors of these literary genres. This multiplication of the autobiographical mode and of the figures of the self seems to result from an ambivalent attitude to self-representation: while the latter is perceived as synonymous with psychic integrity, it is also deeply feared because, freezing the subject, it could prove fatal. Plath’s correspondence with her mother, now available in its entirety thanks to a recent edition, could be compared to a stage: far from giving access to her inner self, it constructs a character, allows us to see in order to better hide. Meticulous descriptions, drawings, press clippings and photographs are part and parcel of a visual universe characterized by excess that questions the very function of letter-writing.